Assessment of health‐related quality of life and how it predicts the outcome of pegylated interferon and ribavirin therapy for chronic hepatitis C. Issue 2 (February 2014) - Matsushita, Hiroshi; Ikeda, Fusao; Iwasaki, Yoshiaki; Seki, Hiroyuki; Nanba, Shintaro; Takeuchi, Yasuto; Moritou, Yuki; Yasunaka, Tetsuya; Onishi, Hideki; Miyake, Yasuhiro; Takaki, Akinobu; Nouso, Kazuhiro; et al.
Abstract Background and Aim Chronic infection with hepatitis C virus (HCV) decreases health‐related quality of life (HRQOL). The present study was planned to investigate the impact of HRQOL of patients with chronic hepatitis C (CHC) on the outcomes of therapy with pegylated interferon and ribavirin (RBV), in addition to IL28B polymorphisms. Methods The present study enrolled 228 CHC patients and assessed their HRQOLs prospectively with the 36‐item short‐form health survey. Results The patients with CHC have lower physical HRQOL status than the general population (P = 0.037, the Z‐test). The patients with advanced liver diseases exhibited further decreases in HRQOL (P = 0.036, Spearman's rank correlation coefficient). The score of total HRQOL was significantly lower in the group with sustained virological response (SVR) to the therapy with pegylated interferon and RBV than the non‐SVR group (P = 0.031, the Mann–Whitney U‐test), with significantly lower scores of mental component and its comprising subscales in the SVR group. Stepwise multivariate logistic regression analysis showed that low HRQOL score ≤ 400 points was significantly associated with SVR (odds ratio = 2.4, P = 0.013), independently from high platelet counts, low HCV RNA, favorable single‐nucleotide polymorphism type of IL28B, and HCV serotype 2. The patients with low HRQOL score will have significantly less decrease in HRQOL score by 4 weeks of the treatment than those with high HRQOL score at baseline (P = 0.0045). Conclusion HRQOL is one of the significant predictor of the outcomes of therapy with pegylated interferon and RBV independently from IL28B polymorphism.